You can't solve it, but you can factor it:
3(2a+1)
2006-12-23 14:27:37
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
What does the book have? You can't solve for "a" because this isn't an equation. You can only factor this expression.
First: find the least common factor > a number that is divisible by 6 and 3 which is 3.
3(2a + 1)
2006-12-23 16:59:03
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
6a + 3 is can be an answer, although you can factor it by dividing through by 3.
You will get:
3(2a + 1)
The quadratic formula does not apply here.
If you set the equation equal to zero, you can solve for the variable a
6a + 3 = 0
6a = - 3 divide through by 6
a = - 1/2
Don't forget to watch your signs when you bring the 3 over to the right side.
2006-12-23 15:07:08
·
answer #3
·
answered by nammy_410 2
·
1⤊
0⤋
you can do a factorization:
6a+3=3(2a+1)
or you can do a quadratic equation
2006-12-23 14:50:57
·
answer #4
·
answered by abbie jameson 1
·
1⤊
0⤋
6a +3 can be anything, depends upon what 'a' is. e.g., if a = 5, 6a + 3 = 6x5+3=33
2006-12-23 14:31:01
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
if u mean
6a + 3 = 0
6a = -3
a = -3/6
a = -1/2
2006-12-23 14:29:43
·
answer #6
·
answered by M. Abuhelwa 5
·
1⤊
0⤋
it's 3(2a+1)
2006-12-23 15:40:55
·
answer #7
·
answered by Bao L 3
·
1⤊
0⤋
9a
2006-12-23 14:35:51
·
answer #8
·
answered by Anonymous
·
0⤊
3⤋